2018
DOI: 10.1007/s00216-018-1148-x
|View full text |Cite
|
Sign up to set email alerts
|

Chiral capillary electrophoresis with UV-excited fluorescence detection for the enantioselective analysis of 9-fluorenylmethoxycarbonyl-derivatized amino acids

Abstract: The potential of capillary electrophoresis (CE) with ultraviolet (UV)-excited fluorescence detection for sensitive chiral analysis of amino acids (AAs) was investigated. dl-AAs were derivatized with 9-fluorenylmethoxycarbonyl chloride (FMOC)-Cl to allow their fluorescence detection and enhance enantioseparation. Fluorescence detection was achieved employing optical fibers, leading UV excitation light (< 300 nm) from a Xe-Hg lamp to the capillary window, and fluorescence emission to a spectrograph equipped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 63 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…CE with UV-excited fluorescence detection for sensitive chiral analysis of amino acids (AAs) was studied by Prior et al [80], employing optical fibers to direct the UV light from a Xe-Hg lamp and the emitted fluorescence to a chargecoupled device (CCD). LODs for enantioseparation of D -AA were in the 10-100-nM range.…”
Section: Optical Detectionmentioning
confidence: 99%
“…CE with UV-excited fluorescence detection for sensitive chiral analysis of amino acids (AAs) was studied by Prior et al [80], employing optical fibers to direct the UV light from a Xe-Hg lamp and the emitted fluorescence to a chargecoupled device (CCD). LODs for enantioseparation of D -AA were in the 10-100-nM range.…”
Section: Optical Detectionmentioning
confidence: 99%
“…The majority of chiral EKC studies reported which separated derivatized enantiomers have combined the derivatization with MEKC analysis, with the aid of an additional chiral selector (i.e., CD), using both chiral [174,182,183] as well as achiral [184][185][186][187][188][189][190][191][192] derivatizing reagents. In an early study, Mechref et al derivatized herbicide compounds with fluorescent tags, followed by CE with CDs and added micellar phases [185].…”
Section: Chiral Separation By Chemical Derivatizationmentioning
confidence: 99%
“…In recent years, one of the most commonly used derivatizing reagents has been FMOC, a popular choice as it yields stable derivatives from rapid reaction with amino compounds. Chiral separations employing FMOC derivatization typically use β-CDs in combination with a surfactant, and have been applied extensively to separate amino acid mixtures [190,192]. Compatibility of derivatization with technological advances, for example, MEKC separations with plastic microchips [178] and integrated sample pretreatment with in-capillary derivatization for high-throughput screening [177], was also demonstrated.…”
Section: Chiral Separation By Chemical Derivatizationmentioning
confidence: 99%
“…In general, various methods such as high performance liquid chromatography (HPLC) [4][5][6][7][8][9], gas chromatography (GC) [10][11][12], and capillary electrophoresis (CE) [13][14][15] are used to separate D/L-amino acids. Currently, LC/MS [16][17][18][19] and multi-dimensional LC having two or more dimensions [20][21][22][23][24][25] are used for this purpose because it is difficult to separate the proteinogenic D/L-amino acids under a single separation mode.…”
Section: Introductionmentioning
confidence: 99%